Increased p66Shc in the Inner Ear of D-Galactose-Induced Aging Mice with Accumulation of Mitochondrial DNA 3873-bp Deletion: p66Shc and mtDNA Damage in the Inner Ear during Aging - Wu, Lisa; Sun, Yu; Hu, Yu-Juan; Yang, Yang; Yao, Ling-Li; Zhou, Xing-Xing; Wang, Hao; Zhang, Rui; Huang, Xiang; Kong, Wei-Jia (PloS one, 2012)
Aging has been associated with mitochondrial DNA damage. P66Shc is an age-related adaptor protein that has a substantial impact on mitochondrial metabolism through regulation of the cellular response to oxidative stress. Our study aimed to establish a D-galactose (D-gal)-induced inner ear aging mouse model and to investigate the potential role of p66Shc and its serine 36-phosphorylated form in the inner ear during aging by using this model. Real-time PCR was performed to detect the mtDNA 3873-bp deletion and the level of p66Shc mRNA in the cochlear lateral wall. Western blot analysis was performed to analyze the total and mitochondrial protein levels of p66Shc and the level of Ser36-P-p66Shc in the cochlear lateral wall. Immunofluoresence was performed to detect the location of the Ser36-P-p66Shc expression in the cochlear lateral wall. The results showed that the accumulation of the mtDNA 3873-bp deletion, total and mitochondrial protein levels of p66Shc and level of Ser36-P-p66Shc were significantly increased in the cochlear lateral wall of the D-gal-treated group when compared to the control group and that Ser36-P-p66Shc was mainly localized in the cytoplasm of the cells in the stria vascularis. During aging, the oxidative stress-related increase of p66Shc and Ser36-P-p66Shc might be associated with the accumulation of the mtDNA 3873-bp deletion in the inner ear.